EFEKTIVITAS MODEL PEMBELAJARAN ECOLITERACY DAN ADAPTASI (ELA) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS BELAJAR - Nur Khasanah, Devi Zakiah; Hermawan Wahyu Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: (1) identify differences in critical thinking skills between fifth-grade students taught using the Ecoliteracy and Adaptation (ELA) learning model and students taught through conventional teaching in Natural and Social Sciences (IPAS) at SD Negeri 1 Padokan; and (2) determine the effectiveness of the ELA learning model in improving students' critical thinking skills. This study was conducted in the 2025/2026 academic year using a quantitative experimental approach with a Non-Equivalent Control Group design. The population consisted of 25 students in grades VA and VB, with 23 students selected as samples and divided into experimental and control groups. Data collection techniques include tests and observations. Statistical analysis includes prerequisite tests, namely normality and homogeneity tests, followed by hypothesis testing using the Independent Sample T test. The results showed that the control group obtained an average score of 48.47 in the pretest and 80.34 in the posttest, while the experimental group obtained an average score of 47.22 and 89.17. A significance value of 0.040 < 0.05 indicates a statistically significant difference. Therefore, the ELA learning model is more effective in improving students' critical thinking skills.